A Herpes Simplex Virus Type 2 Deleted for Glycoprotein D Enables Dendritic Cells to Activate CD4+ and CD8+ T Cells - Retamal-Díaz, Angello R.; Kalergis, Alexis M.; Bueno, Susan M.; González, Pablo A. (Frontiers in Immunology, 2017)
Herpes simplex virus type 2 is highly prevalent in the human population producing significant morbidity, mainly because of the generation of genital ulcers and neonatal encephalitis. Additionally, HSV-2 infection significantly increases the susceptibility of the host to acquire HIV and promotes the shedding of the latter in the co-infected. Despite numerous efforts to create a vaccine against HSV-2, no licensed vaccines are currently available. A long-standing strategy, based on few viral glycoproteins combined with adjuvants recently displayed poor results in a Phase III clinical study fueling exploration on the development of mutant HSV viruses that are attenuated in vivo and elicit protective adaptive immune components, such as antiviral antibodies and T cells. Importantly, such specialized antiviral immune components are likely induced and modulated by dendritic cells, professional antigen presenting cells that process viral antigens and present them to T cells. However, HSV interferes with several functions of DCs and ultimately induces their death. Here, we propose that for an attenuated mutant virus to confer protective immunity against HSV in vivo based on adaptive immune components, such virus should also be attenuated in dendritic cells to promote a robust and effective antiviral response. We provide a background framework for this idea, considerations, as well as the means to assess this hypothesis. Addressing this hypothesis may provide valuable insights for the development of novel, safe and effective vaccines against herpes simplex viruses.